Evidence for an extrinsic immunogen in effective ribosomal vaccines from Salmonella typhimurium. - Hoops, P (1976)
Previous work has indicated that ribosomes isolated from Salmonella typhimurium were highly immunogenic and afforded excellent protection against homologous challenge. Effective protection was obtained also when ribonucleic acid ( RNA) extracted from these ribosomes was used as a vaccine. In this investigation ribosomes prepared by another method and washed repeatedly in 1 M NH1Cl lost much of their prophylactic potency and yielded poorly protective RNA. The high-salt wash of the ribosomes was immunogenic. The RNA and the protein isolated from the salt wash of the ribosomes were effective vaccines. No intrinsic component of the ribosomes was removed by the NH4Cl wash, since the ability of both "crude" and "clean" ribosomes to function equally well in an in vitro protein synthesizing system was demonstrated. The presence of a component with toxic properties similar to those of endotoxin was found in active vaccines but not in weak ones. This was shown by the ability of effective vaccines to kill lead acetate-sensitized mice and to induce tolerance to endotoxin.